Android-Based Biology Learning Media: A Breakthrough to Improve Senior High School Students' Learning Outcomes - Suprapti, Atmi; Wicaksana, Ervan Johan; Sembiring, Dian Arisandy Eka Putra (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to develop an Android-based biology learning media and determine its effectiveness in improving the learning outcomes of 11th-grade high school students on the circulatory system material. The research method used is Research and Development (R&D) with the ASSURE development model. The trial subjects consisted of 6 students for the small group and 18 students for the large group. Validation results from material and media experts indicated that the media was in the “Highly Feasible” category. Teacher and student assessments also showed positive responses with a “Feasible” category. Students' learning outcomes increased significantly after using the developed learning media, as evidenced by the comparison of pretest and posttest scores.